A Note on Stipa Sibirica (L.) Lam., Thr Poisonous Grass of Kashmir - Vaid, K. M. (Indian Forester, 1963)
Slipa sibirica (L.) Lam. grows profusely in the western temperate Himalayas, particularly in the State of Jammu & Kashmir. Its range extends beyond the frontiers and forms almost pure communities under the conifer forests. The grass is notorious for its poisonous properties, causing death to cattle who might feed on it. Cases of severe poisoning to mules of the Defence Forces during military operations in Kashmir have been reported and various expeditions have, in the past, suffered setbacks due to its deleterious contents. The note is of importance on this account especilly when the country’s Forces need every bit of useful information about the area of operation. The note also contains a suggestion about its possible use as a raw material for paper industry.